RETRACTED: Improving the quality of tourist services - Šálková Daniela; Yekimov Sergey; Křečková Renáta; Yarmoliuk Olena; Sobirov Bobur; Oleksenko Roman; Ihnatiev Vitalii (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001